Finitely presentable algebras for finitary monads - Adámek, J.; Milius, Stefan; Sousa, L.; Wißmann, Thorsten (Theory and Applications of Categories, 2019)
For finitary regular monads T on locally finitely presentable categories we characterize the finitely presentable objects in the category of T-algebras in the style known from general algebra: they are precisely the algebras presentable by finitely many generators and finitely many relations.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Finitary functor; Finitely generated object; Finitely presentable object; Regular monad